Unexpectedly low recombination rates and presence of hotspots in termite genomes - Everitt, Turid; Rönneburg, Tilman; Elsner, Daniel; Olsson, Anna; Liu, Yuanzhen; Larva, Tuuli; Korb, Judith; Webster, Matthew T.

(untitled) (Genome Research, 2025)
Meiotic recombination is a fundamental evolutionary process that facilitates adaptation and the removal of deleterious genetic variation. Social Hymenoptera exhibit some of the highest recombination rates among metazoans, whereas high recombination rates have not been found among nonsocial species from this insect order. It is unknown whether elevated recombination rates are a ubiquitous feature of all social insects. In many metazoan taxa, recombination is mainly restricted to hotspots a few kilobases in length. However, little is known about the prevalence of recombination hotspots in insect genomes. Here we infer recombination rate and its fine-scale variation across the genomes of two social species from the insect order Blattodea: the termites Macrotermes bellicosus and Cryptotermes secundus. We used linkage disequilibrium–based methods to infer recombination rate. We infer that recombination rates are close to 1 cM/Mb in both species, similar to the average metazoan rate. We also observe a highly punctate distribution of recombination in both termite genomes, indicative of the presence of recombination hotspots. We infer the presence of full-length PRDM9 genes in the genomes of both species, which suggests recombination hotspots in termites might be determined by PRDM9, as they are in mammals. We also find that recombination rates in genes are correlated with inferred levels of germline DNA methylation. The finding of low recombination rates in termites indicates that eusociality is not universally connected to elevated recombination rate. We speculate that the elevated recombination rates in social Hymenoptera are instead promoted by intense selection among haploid males.